DAMPAK PANDEMI COVID-19 TERHADAP LAYANAN KESEHATAN BALITA - Listiono; Wayan Suriastini; Dani Alfah; Bondan Sikoki; Roni Hermoko; Iip Umar Rifai; Danang Prasetya (Jurnal Keluarga Berencana, 2021)
During the Covid-19 pandemic, toddlers are the age group most vulnerable to the indirect effects of the pandemic but it has negative effects in the long term. This paper aims to analyze the impact of the Covid-19 pandemic on health services for children aged 6-45 months. The total sample in this study is 1,312 children under five who were obtained from a phone survey in one of the sub-districts in Nganjuk Regency. This study finds as many as 78.7% of children under five did not get the supplementary feeding program, about 85.7% of children under five did not receive growth and development monitoring program, and 7.3% of children under five during the pandemic had run out of or lacked drugs/vitamins. Using the Multivariate Logistic Regression, this study finds that the first children under five who did not receive the supplementary feeding program were those who lived in locations where the Posyandu did not open and did not visit or contacted by cadres or health workers. Second, toddlers who did not receive growth and development monitoring were those who live in locations where the Posyandu did not open, were not visited or contacted by Posyandu cadres or health workers, as well as toddlers with caregivers/parents who did not contact cadres/health workers. Third, the impact of the pandemic on household economic conditions and anxiety disorder has caused many children under five to run out of or lack medicines/vitamins. Keywords: Covid-19, children, health care, Posyandu.